Draftof Systematic Performance Management Process Framework - Stříteská, Michaela; Jelínková, Lucie (International Business Information Management Association-IBIMA, 2016)
One key prerequisite for success in today’s tough competitive struggle is the ability to differentiate oneself from the competition. Managers know quite well which areas their companies should focus on in order to achieve greater competitiveness. Yet deficiencies in systems thinking often prevent the company from truly differentiating itself from the competition. Implementing a systems approach is also a key to success in the area of performance measurement and management. A performance management system’s requirements are altered by constant change in business conditions – e.g., changes in the competition, technical and technological development, the values held in the working world or society, or even the attitude towards the environment, which is marked by pressure for a decrease in resource demand. The changes in these requirements are seen primarily in management’s conception and methods, the acquisition of information, and managers’ professional qualifications. Because of the topicality and importance of this subject, this paper is concerned with proposing a systematic process for performance management that incorporates not only a performance measurement and management system but also the factors influencing its quality and a set of tools whose implementation would support the constant improvement of the system as a whole. Subsequently, the possibility of implementing a systematic process of performance management that has been designed in this manner is examined for Czech businesses. A deeper analysis is conducted using case studies in the form of semi-structured interviews at three selected companies.
Návrh rámce systematického procesu řízení výkonnosti
Keywords: performance; management; process; systematical; výkonnost; management; proces; systematický